Exploring the risks of phage application in the environment - Meaden, Sean; Koskella, Britt (Frontiers in Microbiology, 2013)
Interest in using bacteriophages to control the growth and spread of bacterial pathogens is being revived in the wake of widespread antibiotic resistance. However, little is known about the ecological effects that high concentrations of phages in the environment might have on natural microbial communities. We review the current evidence suggesting phage-mediated environmental perturbation, with a focus on agricultural examples, and describe the potential implications for human health and agriculture. Specifically, we examine the known and potential consequences of phage application in certain agricultural practices, discuss the risks of evolved bacterial resistance to phages, and question whether the future of phage therapy will emulate that of antibiotic treatment in terms of widespread resistance. Finally, we propose some basic precautions that could preclude such phenomena and highlight existing methods for tracking bacterial resistance to phage therapeutic agents.